Pelvic floor muscles after birth: Do unstable shoes have an effect on pelvic floor activity and can this be measured reliably? - A feasibility study / Der Beckenboden nach der Geburt: Verändern instabile Schuhe die Aktivität und kann diese reliabel gemessen werden? - Eine Machbarkeitsstudie - Graf Eveline; Borner Barbara; Pehlke Jessica (Sciendo, 2019)
Women often suffer from urinary incontinence after childbirth. Pelvic floor muscle training is an evidenced-based intervention to prevent urinary incontinence and improve its symptoms